2017
DOI: 10.1080/09638288.2017.1340979
|View full text |Cite
|
Sign up to set email alerts
|

Staffs’ documentation of participation for adults with profound intellectual disability or profound intellectual and multiple disabilities

Abstract: A deeper focus on participation in the implementation plans and all life areas in the component Activities and participation is needed. It is important that the documentation clearly shows what the adult wants, wishes, and likes in everyday life. It is also important to ensure that the job description for staff contains both life areas and individual preferences so that staff have the possibility to work to fulfill social and individual participation for the target group. Implications for rehabilitation There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…In addition, no efforts were made to change or introduce new social roles for adults with VSPID that could enhance their participation. These findings are in line with those of other studies, which also showed that direct support professionals (DSPs) in residential facilities experience difficulty developing new social roles for individuals with intellectual disabilities [17,18]. Because adults with severe or profound intellectual disabilities are highly dependent on their environment and the support they receive from others [3], a possible explanation for their limited participation could lie in the attitudes and resources of DSPs.…”
Section: Introductionsupporting
confidence: 90%
“…In addition, no efforts were made to change or introduce new social roles for adults with VSPID that could enhance their participation. These findings are in line with those of other studies, which also showed that direct support professionals (DSPs) in residential facilities experience difficulty developing new social roles for individuals with intellectual disabilities [17,18]. Because adults with severe or profound intellectual disabilities are highly dependent on their environment and the support they receive from others [3], a possible explanation for their limited participation could lie in the attitudes and resources of DSPs.…”
Section: Introductionsupporting
confidence: 90%
“…In addition, no efforts were made to change or introduce new social roles for adults with VSPID that could enhance their participation. These findings are in line with the results of a study of Talman, Gustafsson, Stier, and Wilder [20], which also showed that support professionals find it difficult to define potential roles for adults with profound intellectual (and multiple) disabilities. The importance of social roles have previously been described by Wolfensberger [21].…”
Section: Introductionsupporting
confidence: 87%
“…This emphasis on varying roles that such individuals can assume within and outside the residential facility may induce changes in the attitudes of DSPs regarding the possibilities, opportunities, and activities that apply to the adults with VSPID with whom they work. The importance of attitudinal changes has been demonstrated in a study conducted by Talman et al [20], who found that DSPs experience difficulty in developing new roles for individuals with profound intellectual disabilities. Experiences of implementing the preliminary version of the CFP+ intervention revealed that as a result of the intervention, DSPs focused more on possibilities and less on the disabilities of adults with VSPID.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DSPs’ views on the inclusion of individuals with intellectual disabilities considered as a component of participation according to the aforementioned definition reportedly influence their associated efforts (Venema, Otten, & Vlaskamp, 2015). Other studies have shown that the DSPs of individuals with severe or profound intellectual disabilities find it difficult to apply inclusive principles (Bigby, Clement, Mansell, & Beadle‐Brown, 2009) or to identify activities that match the roles of this target group (Talman, Gustafsson, Stier, & Wilder, 2017). Because of the limitations of adults with VSPID, DSPs may be inclined to focus on these limitations and care tasks and less on the capabilities, wishes and participation of such individuals (McConkey & Collins, 2010).…”
Section: Introductionmentioning
confidence: 99%